Bridging Education To Innovation Through Entrepreneurial Orientation and Self-Efficacy: A Self-Determination Theory Perspective - Suparno, Antoni; Radianto, Wirawan Endro Dwi; Dewi, Liliana (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: Entrepreneurial education (EE) has become a central topic in emerging economies; however, its interaction with entrepreneurial orientation (EO), entrepreneurial self-efficacy (ESE), and innovation capability (IC) remains underexplored, particularly in the Indonesian context. By positioning EO as a mediator and ESE as both a direct and moderating factor, this study extends prior research and provides a more integrative understanding of entrepreneurial behavior.Purpose: This study analyzes the role of entrepreneurial education in enhancing innovation capability by analyzing entrepreneurial orientation as a mediator and entrepreneurial self-efficacy as a moderator within the framework of Self-Determination Theory.Design/methodology/approach: The study employs a survey-based design with 166 valid responses analyzed using PLS-SEM, which allows testing of complex mediating and moderating effects simultaneouslyFindings/Result: The findings reveal that entrepreneurial education significantly boosts both entrepreneurial orientation and innovation capability. Entrepreneurial orientation mediates the impact of education on innovation by encouraging proactive, innovative, and risk-taking behaviors. As evidenced by the analysis, entrepreneurial self-efficacy demonstrated a substantial and direct impact on both the orientation towards entrepreneurship and the ability to innovate but did not show significant moderating effects.Conclusion: This study contributes theoretically by extending SDT through the integration of EO and ESE into the EE–IC relationship while empirically demonstrating the strong predictive power of the proposed model. From a practical perspective, the results suggest the importance of embedding EO-building experiences and ESE-enhancing interventions in entrepreneurship education, supported by policies that foster innovation ecosystems. Future research could expand this framework across different cultural and industrial settings.Originality/value (State of the art): This study offers a novel integrated model connecting educational, psychological, and behavioral constructs, contributing to the existing literature by addressing gaps in previous research and offering practical insights for entrepreneurship education in emerging markets.Keywords:   entrepreneurial education, entrepreneurial orientation, innovation capability, entrepreneurial self efficacy, entrepreneur by design